Research Activities in Biochemistry, Genetics and Molecular Biology during 1998-2007 in India: A Scientometric Analysis - Bala, Adarsh; Gupta, B.M. (DESIDOC Journal of Library & Information Technology, 2010)
This study attempts to analyse the research profile of biochemistry, genetics and molecular biology research in India during 1998-2007, country’s performance based on its research output, its publication share and rank in global context, and annual publication growth rate. It also analyses the share of international collaborative papers in India’s research output, the characteristics of research output of major Indian institutions, authors, and highly-cited papers. The patterns of research communication by Indian scientists in most productive journals in this discipline have also been evaluated. DOI: 10.14429/djlit.30.278